The Effects of a 6-Week Swimming Intervention on Gross Motor Development in Primary School Children - Nicole A. Pratt; Michael J. Duncan; Samuel W. Oxford (MDPI AG, 2023)
(1) Background: This study examines the effects of a 6-week swimming intervention on motor competence in children. (2) Methods: A total of 107 children (n = 52 boys, n = 55 girls) aged 7.8 ± 0.63 years that were recruited from five primary schools in central England participated in this study, undertaking either an aquatic intervention once a week for six weeks or acting as a control group completing their usual physical education program. Participants underwent pre- and post-assessments of general motor competence using the Test of Gross Motor Development, Third Edition (TGMD-3) (a process measure) and a composite of 10 m running sprint time and standing long jump distance (product measures). Aquatic motor competence was assessed via the Aquatic Movement Protocol (AMP). Fear of drowning and swimming opportunities were also assessed by implementing a questionnaire. (3) Results: Following a mixed-model ANOVA, an overall main effect was found from pre (40.05 ± 13.6) to post (48.3 ± 18.6) for TGMD-3 scores (p < 0.05) and pre (38.7 ± 31.7) to post (50.6 ± 36.8) for AMP scores (p = 0.001). A negative significant relationship was found between AMP scores with both fear of water (p = 0.01) and fear of drowning (p < 0.05). A positive significant relationship was found between swimming opportunities and AMP score (p = 0.001). (4) Conclusions: The aquatic-based intervention improves not only aquatic motor competence but also transfers improvements in dryland movement competencies. Future research should look to implement control groupings which do not participate in swimming to further investigate the difference between swimmers and non-swimmers; however, due to swimming being a part of the national curriculum in England, this may not be feasible.